Modelo para la Detección de Ataques de DDoS en Servidores de Nombres de Dominios sobre un Retorno de Simulación en la Red de la Universidad Nacional de Chimborazo 2018 - Bonifaz Herrera, Dany Xavier (2019)
At present, the security of computer systems has increased in conjunction with the evolution and advancement of technology, where data and information protection is very relevant to the development of a company. Distributed denial-of-service (DDoS) attacks disrupt services through excessive resource consumption on the server. The aim of this research was to develop a security model for the detection of DDoS attacks on domain name servers on a simulation environment, to determine which mechanisms are appropriate to mitigate this attack on a network of The UNACH and development of a guide for its application on a real environment. The methodology used in this research is longitudinal study, since data were obtained at different times during a given period, in order to examine their variations over time. for which, measurement parameters were analyzed and identified as: The quantity of packages processed per day, the level of vulnerability by DDoS attacks and the response time of the server. For the verification of the hypothesis, the T-STUDENT statistical test was used for related samples, for this reason according to the results obtained thanks to our model for the detection of DDoS attacks; Based on the vulnerabilities detected in the network of the National University of Chimborazo, it is concluded that security can be improved by at least 65%.